Hyperchaos in convection with the Cattaneo-Christov heat-flux model - Daumann C.C.* (2019)
© 2019, EDP Sciences / Società Italiana di Fisica / Springer-Verlag GmbH Germany, part of Springer Nature.Abstract: In this paper, we report on the nonlinear dynamics of a five-variable, four-parameter system, which models the effects of thermal relaxation time on Rayleigh-Bénard convection of Boussinesq fluid layer heated underneath. Six cross-sections of the four-dimensional parameter-space are considered. By using Lyapunov exponents spectra to characterize the dynamical behavior at each point of each these diagrams, we show that different parameter regions are allowed, from equilibrium points to chaos and hyperchaos regions.